1991
DOI: 10.1073/pnas.88.13.5799
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and membrane-binding properties of a signal sequence are largely unaltered by its adjacent mature region.

Abstract: We have synthesized a peptide corresponding to the 25-residue signal sequence plus the first 28 residues ofthe Escherichia coli outer membrane protein LamB in order to explore the properties ofa signal sequence in the presence of the N-terminal region of its passenger. In the last few years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…23 Intriguingly, mutations in the early region of a passenger protein can abolish correct targeting, implying that there are restrictions on the allowed sequences of secreted proteins (e.g., Ref. 24).…”
Section: Signal Peptide Conformations and Membrane Interactionsmentioning
confidence: 99%
“…23 Intriguingly, mutations in the early region of a passenger protein can abolish correct targeting, implying that there are restrictions on the allowed sequences of secreted proteins (e.g., Ref. 24).…”
Section: Signal Peptide Conformations and Membrane Interactionsmentioning
confidence: 99%
“…Apparently, binding of the precursor to liposomes is mediated primarily by interactions with the presequence peptide. Although this is the first study comparing the lipid binding properties of an authentic mitochondrial precursor protein and its presequence peptide, similar studies using a secretory bacterial protein (42,50) also concluded that the mature portion of the precursor protein did not have any effect on the binding of the signal peptide to lipids. In our case, the only difference detected between the presequence peptide and the precursor was on the kinetics of carboxyfluorescein release from liposomes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these were conducted with constructs containing motifs around the cleavage site that differed markedly in their primary structure, appended to distinct passenger molecules. 1,23 A mammalian globular cytochrome b 5 (Cyt) tagged with(out) the alkaline phosphatase SS of E. coli has been exploited to investigate many diverse molecular features of high-level periplasmic protein secretion. 18,[24][25][26][27][28] It has proved an invaluable tool in reporting both the in vitro and in vivo sec-dependent status of recombinant protein generation by visual and spectroscopic means.…”
Section: Introductionmentioning
confidence: 99%